2015
DOI: 10.18489/sacj.v56i1.209
|View full text |Cite
|
Sign up to set email alerts
|

The factors that influence customer e-services adoption

Abstract: The aim of this paper is to provide an overview of the investigation into customer e-service adoption. The investigation includes a qualitative survey and observation of participants using e-services. E-services are used to attract customers and persuade them to transact online and the customer’s perception of an e-service contributes greatly to e-service adoption or rejection. This paper describes the factors that influence customer perception towards e-services. Relationships between the identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…Social media system availability significantly influences overall service quality in the South African banking industry. This finding validates studies conducted by Kim (2015), Persad and Padayachee (2015) and Quach et al (2016), who revealed similar findings. Therefore, the study concludes that a bank's Facebook page availability plays a significant role in shaping social media sites.…”
Section: Social Media System Availabilitysupporting
confidence: 93%
“…Social media system availability significantly influences overall service quality in the South African banking industry. This finding validates studies conducted by Kim (2015), Persad and Padayachee (2015) and Quach et al (2016), who revealed similar findings. Therefore, the study concludes that a bank's Facebook page availability plays a significant role in shaping social media sites.…”
Section: Social Media System Availabilitysupporting
confidence: 93%
“…Lastly, the occurrence of technostress is highly related to the overall information management of the used website and the required cognitive demand. In that regard, specifically information overload, opacity, irrelevance, or insufficiency have shown to be antecedents of technostress [17,18,43].…”
Section: The Relevance Of Technostress In the Context Of E-commercementioning
confidence: 99%
“…Another component -in the field of consumer research fundamentally important -is the behavioral consequence that consumers draw following technology-induced stress. The experience of technostress has shown to be associated with behavioral responses of flight and avoidance in the shape of shopping cart abandonment, purchase cancellation and the general rejection of e-services, turning to alternative providers, to mitigate and evade the stressful situation [17,18,19].…”
Section: The Relevance Of Technostress In the Context Of E-commercementioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of conditions that are not desired by consumers is the core of risk perception; this is closely related to consumer behavior. Associated with online transactions, risk perception is described as a reluctance (there is no motivation) consumers to make online transactions due to concerns and uncertainties that are more likely to transact conventionally or offline (Persad and Padayachee, 2015). The risk experienced by consumers due to the possibility that the product selected may fail to meet needs is referred to as product risk or product risk (Abrar et all., 2017).…”
Section: Millennial Generationmentioning
confidence: 99%